Synthesis and Characterization of Sio₂ Thin Films Derived from Rice Husk Ash Coated with Cuo: Evaluation of Photocatalytic Activity through Methylene Blue Degradation - Afra Hayyunnisa; Riri Jonuarti; Yenni Darvina; Fadhila Ulfa Jhora (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Water pollution caused by synthetic dye effluents that resist natural degradation has intensified the need for stable and environmentally sustainable photocatalytic materials. This study aimed to synthesize and characterize bilayer SiO₂/CuO thin films using silica extracted from rice husk ash (RHA) and to evaluate their photocatalytic activity for methylene blue (MB) degradation. Silica was extracted from agricultural RHA, activated with 1 M HCl, fabricated into thin films through sol–gel and spin-coating techniques, and thermally annealed at 300 °C. X-ray diffraction analysis confirmed the amorphous structure of silica, indicated by a broad diffraction hump centered at 2θ ≈ 22°, and the formation of monoclinic CuO crystalline phases in the bilayer films. Cross-sectional scanning electron microscopy showed that the pure SiO₂ film had a smooth morphology and a thickness of 3.507 µm, whereas the bilayer SiO₂/CuO film had a total thickness of 5.444 µm and exhibited a distinct porous upper layer comprising accumulated CuO grains deposited on the smooth SiO₂ base layer. Under UV-A irradiation, MB absorbance at λ = 664 nm decreased continuously, resulting in a degradation efficiency of 12.13% after 180 min. The degradation process closely followed pseudo-first-order kinetics, with a rate constant of 7.33 × 10⁻⁴ min⁻¹ and R² = 0.985. These findings demonstrate that biomass-derived silica from RHA can function as a supporting matrix for anchoring photocatalytically active CuO granular structures. This study contributes to the sustainable utilization of agricultural waste and provides a foundation for the further development of biomass-derived thin-film photocatalysts for synthetic dye degradation.